Caribbean Report 20-02-1997 - Gordon, Warren (anchor); Richards, Ken (correspondent); Newens, Stanley; Niles, Bertram (anchor); Thompson, Julia (correspondent); Panday, Basdeo (interviewee); Assam, Mervyn (interviewee); Walker, Andrew (correspondent); Rohee, Clement (interviewee) (The British Broadcasting Corporation, 1997)
bThe EC proposal to cut the share of the EU banana market allotted to ACP countries has been approved by the European Parliament. The proposal must now go before the Council of Ministers for final approval. Next, in a summit in Antigua, President Leonel Fernandez, of the Dominican Republic has told Caribbean leaders that they should forget about the idea of preferences in their international trade relations. Instead they should focus on a package of other measures such as debt relief. In the following segment, Presidents of the Dominican Republic and Haiti have briefly met during the summit, to discuss the issue of the deportation of thousands of Haitians. Other Heads of government were busy trying to reach decisions of regional and international matters which impact on foreign relations and other specific areas. Next, the Director General of the World Trade Organisation has appointed a panel to rule in the dispute between the United States and the European Union about US sanctions against Cuba. According to the European Union the Helm-Burton law breaks world trade organisation rules. In the final segment, the Foreign Minister of Guyana is dismissing talks of a long term successor for the ailing President, Dr Cheddi Jagan. He is in hospital, at the Walter Reed Army Medical Center in Washington DC, where he is covering from a heart attack.
1. Headlines (00:00-00:30)
2. The European Parliament has approved the proposal to cut the share of the EC market for ACP banana producers. Ken Richards interviews European Member of Parliament, Stanley Newens (00:31-03:51)
3. Caribbean leaders told to forget about trade preferences in this day and age. Bertrand Niles reports from St. John (03:52-06:05
4. President Fernadez and Preval met briefly to discuss the issue of the deportation of thousands of Haitians. Basdeo Panday, Prime Minister of Trinidad and Tobago, Mervyn Assam, Trade Minister of Trinidad and Tobago and Premier Vance Amory are interviewed. Julia Thompson reports (06:06-10:02)
Keywords: European Parliament.; Banana market -- European Union.; Council of Ministers.; Fernandez, Leonel.; Deportees -- Haitian.; Caricom Summit -- Antigua.; World Trade Organisation.; Ruggiero, Renato; Sanctions -- United States.; European Union.; World trade rules.; Jagan, Cheddi.